Adaptive learning and multiple equilibria in a natural rate monetary model with unemployment persistence - Anssi Rantala (Bank of Finland, 2003)
This paper demonstrates that the adaptive learning approach to modelling private sector expectations can be used as an equilibriumselection mechanism in a natural-rate monetary model with unemployment persistence.In particular, it is shown that only one of the two rational expectations equilibria is stable under least-squares learning, and that it is always the low-inflation equilibrium with intuitive comparative statics properties that is the learnable equilibrium.Hence, this paper provides a basic theoretical justification for focusing on the lowinflation equilibrium.Earlier contributions, in which the high-inflation equilibrium was ignored, mainly because of its unpleasant characteristics, are not theoretically satisfactory.
URN:NBN:fi:bof-20140807109
Keywords: C62; D83; D84; E52; 330; adaptive learning; monetary policy; multiple equilibria; persistence